Homelessness across Alaska, the Canadian North and Greenland: A Review of the Literature on a Developing Social Phenomenon in the Circumpolar North - Christensen, Julia; Arnfjord, Steven; Carraher, Sally; Hedwig, Travis (ARCTIC, 2017)
Over the past three decades, homelessness has become an area of significant social concern in Alaska, the Canadian North, and most recently, Greenland. These three geographical contexts show both similarities and contrasts, but no effort has yet been made to review the research literature on homelessness from these three regions or to highlight key themes or gaps in current knowledge. We reviewed the literature in order to 1) understand the current state of knowledge of the dynamics of homelessness in Alaska, the Canadian North (here including Yukon, Northwest Territories, and Nunavut), and Greenland and 2) conceptualize a northern geography of homelessness. The research literature identifies common themes across these contexts, which include chronic housing insecurity, overrepresentation of Indigenous peoples among those living homeless, and the significance of gendered experiences of homelessness. It identifies key interconnections between hidden homelessness and visible homelessness as the dynamics of urbanization in northern towns and cities reveal the social consequences of chronic housing insecurity in settlements. Across these northern regions, the high rates of chronic homelessness reflect the prevalence of northern housing insecurity and the lack of both adequate, appropriate support for people experiencing mental health or addiction problems and supportive or public housing options. Strategies that aim to diversify housing stock at various critical points along the housing spectrum are needed in northern regions, an idea that is promoted by Housing First and transitional housing programs in Alaska and the Canadian North. Au cours des trois dernières décennies, le sans-abrisme est devenu une grande préoccupation sociale en Alaska, dans le Nord canadien et, plus récemment, au Groenland. Ces trois contextes géographiques présentent des similitudes et des différences, mais aucun effort n’a encore été déployé pour examiner la documentation de recherche sur le sans-abrisme dans ces trois régions ou pour ...